Effects of self-selected versus motivational music on lower limb muscle strength and affective state in middle-aged adults - Greco, Francesca; Rotundo, Luca; Grazioli, Elisa; Parisi, Attilio; Carraro, Attilio; Muscoli, Carolina; Paoli, Antonio; Marcolin, Giuseppe; Emerenziani, Gian Pietro (PeerJ, 2022)
Background Strength training plays a crucial role in promoting healthy ageing and music might affect how individuals perform and perceive strength exercises. This study aimed to investigate the effects of self-selected music (SSM) on muscle strength and affective states during maximal isometric contractions on a customized leg extension. Methods Twenty-six healthy middle-aged males (50.8 ± 8.4 years) performed maximal and endurance isometric strength tests under three different conditions: SSM, motivational music (MM), and control condition (CC). Peak force and Rate of Force Development (RFD) were assessed during the maximal isometric strength test. The isometric endurance test evaluated the mean force and a fatigue index. Moreover, Felt Arousal Scale (FAS) was administered before the strength protocol, whereas the Rate of Perceived Exertion (RPE) and Feeling Scale (FS) at the end of it. Results Mean force was significantly higher in the SSM (507.3 ± 132.2 N) than MM (476.3 ± 122.4 N, p < 0.01) and CC (484.6 ± 119.2 N, p = 0.03). FAS was significantly higher in the SSM (4.0 [1.3] than MM (3.0 [2.3], p < 0.01) and CC (3.0 [1.3], p < 0.01) conditions. FS was significantly higher in the SSM (4.0 [2.0] than MM (3.0 [1.3], p < 0.01) and CC (3.0 [1.3], p < 0.01) conditions. No significant differences were found for peak force, RFD, fatigue index, and RPE. Conclusions Listening to SSM seems to influence isometric endurance strength performance in middle-aged adults positively. Moreover, listening to SSM might improve individuals’ affective states without affecting the level of perceived exertion.
Keywords: Exercise; Endurance; Resistance; Motivation; Ageing